A world review of the bee fly tribe Usiini (Diptera, Bombyliidae) — Part 3: Parageron Paramonov s. lat. ‒ Corrigendum - Gibbs, David (European Journal of Taxonomy, 2024)
The present corrigendum corrects a nomenclatural error regarding Apolysis bicolor (Efflatoun, 1945) comb. nov. in the “Excluded species” section Gibbs (2023: 148).